Hadith #153 - Sunan Ibn Majah - Abdul 'Aziz bin Syah al-'Asady عبد العزيز بن سياه; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“The Messenger of Allah performed ablution washing each part once. He said: ‘This is the ablution of the person from whom Allah will not accept his prayer without it.’ Then he performed ablution washing each part twice, and he said: ‘This is the ablution that Allah appreciates.’ Then he performed ablution washing each part three times, and said: ‘This is how ablution is performed properly, and this is my ablution and the ablution of the Close Friend of Allah, Ibrahim. Whoever perform
Grade: